Value stream mapping: a tool to design the future state map aligned with lean manufacturing principles - Esfandyari , Alireza; Osman, Mohd Rasid; Ismail, Napsiah; Megat Ahmad, Megat Mohamad Hamdan (Federation of Engineering Institutions of Islamic Countries, 2006)
For the last few years almost every manufacturing industry has been trying to get "lean". A headlong rush to offer value to the customers by becoming lean and responsive has created urgency for researchers and practitioners to apply new tools and techniques to address various wastes. The process of mapping the material and information flows of all components and sub-assemblies in a value stream that includes manufacturing, suppliers and distribution to the customer is known as value stream mapping (VSM). VSM has proved effective in identifying and eliminating wastes in a facility with similar or identical product routings, such as assembly facilities. It is the aim of this paper is to illustrate how Value Stream Mapping (VSM) and its associated tools can be used to design a desired future state aligned with lean manufacturing principles. Non value-added activities that cause the waste are described and needed data to develop the current state map are introduced. At the next step the improvements and the procedures to mapping the future state is provided. The main prerequisite is realizing the gaps between the current and ideal stream of information and materials in the shop floor. The metrics and methods are enhanced as guidelines to achieve the stream without waste. Some beneficial of value stream mapping are highlighted.